Numerical analysis of surface integrity in parallel turning process Part I: Influence of cutting tool parting distance. Issue 1 (June 2020) - Kanakaraju, Veldi; Hassan, Faisal; Rathinam, Kalidasan; Norkey, Gavendra
Abstract: Surface integrity is one among the prime quality features of turned parts. In the present research work, surface residual stress generated during parallel turning is analysed numerically using finite element method based software. Parting of cut-chip from uncut-work material is dealt by Johnson-Cook criteria. Tool-chip friction was modelled by penalty contact method. Cutting tool parting distance is an important process parameter in parallel turning. The main objective of the current research work is to evaluate the significance of parting distance on axial and circumferential surface residual stresses induced on machined work surfaces. The analysis revealed that with the increment in parting distance, the surface integrity raised. When the distances was raised from 0.4 to 0.8 mm, for a cutting velocity of150 m/min and feed 0.2 mm/rev the axial and circumferential residual stresses elevated by 34% and 33% for surface machined by second tool. For all chosen parting distances, the stresses raised with the increase in cutting velocity. Parallel turning was advantageous in increasing the machined surface integrity.